By the numbers - Lancaster, Jen, 1967- (New York, New York : New American Library, 2016)
"The New York Times bestselling author of The Best of Enemies serves up a hilarious new novel of the "sandwich generation." Actuary Penny Sinclair has a head for business, and she always makes rational decisions. Knowing that 60% of spouses cheat and 50% of marriages end in divorce, she wasn't too surprised when her husband had an affair. (That he did so with a woman their daughter's age? Well, that part did sting a bit.) She just made sure she got everything in the divorce, including their lovely old Victorian house. And as soon as her middle daughter has her hipster-fabulous wedding in the backyard, she's trading it in for a condo in downtown Chicago... Well within the average market time in her area, Penny gets an offer on the house. But then life happens. Her children, her parents and her ex come flying back to the nest, all in need of Penny's emotional--and financial--support. Spread thin, Penny becomes the poster child for the "sandwich generation," when all she really wanted to do was make managing director, buy a white couch, and maybe go on a Match.com date.."--
Keywords: Sandwich generation -- Fiction; Divorced women -- Fiction; FICTION / Humorous; FICTION / Contemporary Women; FICTION / Family Life; Domestic fiction; Humorous fiction